A COMPARATIVE STUDY BETWEEN CLONIDINE AND DEXMEDETOMIDINE AS AN ADJUVANT TO BUPIVACAINE IN BRACHIAL PLEXUS BLOCK THROUGH USG-GUIDED AXILLARY APPROACH - SUNDARI, MANTHA RADHA; SUBBALAKSHMI, TELIDEVARA DURGA POORNA; PRASAD, TVVSV (International Journal of Current Pharmaceutical Research, 2024)
Objective: To improve the quality of block in regional anaesthesia, several adjuvants are added to local anaesthetic drugs. The effects of clonidine and dexmedetomidine were compared with regard to the onset and duration of sensory and motor block as well as the length of analgesia when used as an adjuvant to bupivacaine in brachial plexus block by axillary approach. Objective: The present study was conducted to compare the onset time, duration and analgesic efficacy of clonidine vs dexmedetomidine when added as adjuvant to bupivacaine (0.5%) for USG guided brachial plexus by axillary approach. Methods: This is a prospective, randomized; comparative study conducted in elective unilateral upper limb forearm and hand surgeries. The study was conducted at Government General Hospital, Srikakulam, between March 2023 to September 2023 after obtaining permission from the Institutional Ethics Committee and from the patients. Group BC received 30 ml of 0.5% bupivacaine with Clonidine 1µg/kg (n=30) and Group BD received 30 ml of 0.5% bupivacaine with dexmedetomidine 1µg/kg (n = 30). The onset and duration of sensory and motor block total duration of analgesia were studied in both groups. Results: The mean time for onset of sensory block in Group BD was 4.7 min, which was lower than Group BC 8.47 min. The mean time for onset of motor block in Group BD was 9.63 min the mean time for total duration of sensory block in Group BD was 537.8 min. This was higher than the Group BC 319.1 min. The total duration of analgesia in Group BD was 666.27 min. This was higher than in Group BC 375.23 min. Bupivacaine dexmedetomidine group had better quality analgesia than the bupivacaine clonidine group. Conclusion: The addition of Dexmedetomidine (1μg/kg) to bupivacaine (0.5%) in brachial plexus block by USG-guided axillary approach results in a shorter onset time for sensory and motor blockade, prolongs the duration of sensory and motor blockade and also total duration of analgesia.